ESTIMATION OF WASTE AND ITS MANAGEMENT STRATEGIES IN THE MODERN FISH MARKET OF MUARA BARU JAKARTA - Muninggar, Retno; Rifqi, Hafizh Syah; Purwangka, Fis; Riantoro, Mhd Rizki (Marine Fisheries : Journal of Marine Fisheries Technology and Management, 2025)
Modern Fish Market is one of the main fish marketing and culinary tourism centers located in Muara Baru, Jakarta, specifically within the Nizam Zachman Ocean Fishing Port area. The market faces environmental challenges related to solid waste, particularly the mismanagement of inorganic waste. This study aims to estimate the amount and economic value of waste produced, compare existing waste management practices with SNI-19-2454-2002, and formulate appropriate waste management strategies for Modern Fish Market. The research was conducted using a case study approach, and respondents were selected through accidental sampling and purposive sampling techniques. Data were analyzed using descriptive analysis, gap analysis, and SWOT analysis. The results showed that waste generated from fish marketing activities at PIM consisted of 3.95% organic waste and 96.05% inorganic waste, with the economic value of inorganic waste reaching Rp1,559,000 per day. In terms of waste management, two aspects were found to be inconsistent with SNI-19-2454-2002. Six strategies were recommended to improve waste management at Modern Fish Market, with priority actions including the preparation of technical guidelines aligned with SNI-19-2454-2002 and expanding cooperation with recycling industries.Keywords:       recycling, organic waste, inorganic waste, SNI-19-2454-2002, Nizam Zachman